PEMBUATAN MEDIA PEMBELAJARAN BERBASIS MOBILE LEARNING PADA MATERI ZAT DAN KARAKTERISTIKNYA UNTUK SISWA SMP KELAS VII - Afiqah, Nurul; Ma'aruf, Zuhdi; Rahmad, M. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract :Mobile learning is a learning media that uses technological devices such as mobile phones, laptops, etc. With mobile learning, students can access educational content easily. The research conducted aims to make learning media inthe form of mobile learning media substances and their characteristics that can be accessed boldly. The type of research used is Research and Development (R&D) using the ADDIE model which only consists of 4 stages, namely the stages of design analysis, development and evaluation. The data needed are quantitative data, namely 1) questionnaire respondent data about the need for learning resources distributed to students, 2) mobile learning media assessment assessment data with validators, and 3) small-scale mobile learning media score data. The results showed that the average score of the overall validation of the mobile learning media was in the good category, namely 3.37 and the overall small-scale test result was 3.92 with a very good category. So that it can be said that the mobile learning-based learning media on the material and characteristics in SMP class VII have valid all aspects of both content, presentation, language and graphics, and mobile learning is appropriate to be used as a learning resourcein science learning in SMP.Keywords:Learning Media, Mobile Learning Media, Substances and Their Characteristics